2020
DOI: 10.1007/s10014-020-00365-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse midline glioma of the cervical spinal cord with H3 K27M genotype phenotypically mimicking anaplastic ganglioglioma: a case report and review of the literature

Abstract: Here, we report on a 28-year old male patient presenting with neck and shoulder pain, dysesthesia of all four limbs and hypesthesia of both hands, without motor deficits. Magnetic resonance imaging showed an intradural, intramedullary mass of the cervical spinal cord of 6.4 cm length and 1.7 cm diameter. The patient underwent surgical resection. Histological and immunohistochemical evaluation showed pleomorphic glial tumor cells, mitoses, calcifications, and atypical ganglioid cells compatible with the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It was worth noting, however, that the initial MRI presentation of the five patients all resembled a low-grade CNS tumor, which easily led to being misdiagnosed as benign tumors at the initial diagnosis, potentially delaying treatment. In case of a 25-year-old women ( 22 ) and a 28-year-old man ( 23 ), the DMG-H3K27m tumors were located in the cervical medulla, mimicking the manifestations of meningioma and ganglioneuroma on the images respectively. Other studies have suggested that patients with suspected gliomas at midline sites on MR should first undergo immunohistochemistry testing for H3K27M mutations, especially if tissues were difficult to collect and malignancy is difficult to diagnose based on histological examination alone ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was worth noting, however, that the initial MRI presentation of the five patients all resembled a low-grade CNS tumor, which easily led to being misdiagnosed as benign tumors at the initial diagnosis, potentially delaying treatment. In case of a 25-year-old women ( 22 ) and a 28-year-old man ( 23 ), the DMG-H3K27m tumors were located in the cervical medulla, mimicking the manifestations of meningioma and ganglioneuroma on the images respectively. Other studies have suggested that patients with suspected gliomas at midline sites on MR should first undergo immunohistochemistry testing for H3K27M mutations, especially if tissues were difficult to collect and malignancy is difficult to diagnose based on histological examination alone ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic analysis was performed by extracting DNA from FFPE material using the Maxwell system (Promega) according to the manufacturer’s protocol and subsequent application of the Illumina Focus Panel (Illumina) on an Illumina MiniSeq device (Illumina) according to the manufacturer’s protocols enabling us to analyze 41 genes in parallel, including IDH1 and IDH2 hot spot regions (the complete gene list can be found in Table 1 ). Hot spot loci of TERT promoter were analyzed by Sanger sequencing [ 4 , 7 ]. DNA-methylation profiling was performed using Illumina EPIC bead chips that were scanned on an Illumina NextSeq 550DX device.…”
Section: Molecular Genetic Profilingmentioning
confidence: 99%
“…Molecular genetic analysis was performed as previously described. 10 Analysis showed a mutation of the TERT promoter region (C228T) and a PTPN11 p.G60R mutation (Figure 3A). There was no mutation at the further analyzed 52 genes (Figure 3B).…”
Section: Pathological Findingsmentioning
confidence: 99%